HIGIENE DAN SANITASI TERMINAL PELABUHAN RORO KOTA DUMAI TAHUN 2012 - Sri Rezeki Pulungan; Irnawati Marsaulina; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
Hygiene and sanitasion roro Dumai port terminal in 2012. Port of a node meeting or activity in and out of boats, goods and people and the spread of disease as well as the transformation of the gate. Ports is a global threat to public health due to the presence of quarantine diseases, new infectious diseases, and infectious diseases recur old. So to achieve a healthy harbor, then please be aware of hygiene and sanitation aspects of port terminals.This study aims to determine the hygiene and sanitation Roro Dumai port terminals. This type of research is descriptive simple to see the picture of hygiene and sanitation Roro port terminal Dumai City in 2012. The result showed that water supply, sewage disposal facilities, waste disposal, vector eradication and food sanitation cafeteria / restaurant in the port roro terminal does not meet the health requirement. Water supply, sewage disposal, garbage disposal, vector eradication and food sanitation in Roro port terminals do not meet the health requirement. Suggested to port health office class III should make efforts to improve hygiene and sanitation in Dumai City Roro port terminal, the employee should implement and run the program of hygiene and sanitation to achieve a qualified health port and port health office class III should supervise the implementation efforts hygiene and sanitation in Dumai City Roro port terminals in order to improve and achieve healthy harbor. Keywords: Hygiene, Sanitation, Port RoroTerminal